Physical Activity and Sedentary Behavior in University Students–The Role of Gender, Age, Field of Study, Targeted Degree, and Study Semester - Edelmann, Dennis; Pfirrmann, Daniel; Heller, Sebastian; Dietz, Pavel; Reichel, Jennifer L.; Werner, Antonia M.; Schäfer, Markus; Tibubos, Ana N.; Deci, Nicole; Letzel, Stephan; Simon, Perikles; Kalo, Kristin (Frontiers in Public Health, 2022)
Background Physical inactivity and sedentary behavior are modifiable risk factors for an unhealthy lifestyle in university students. The aim of this study was to identify subgroups among German university students with an increased risk for unhealthy behavior. For this purpose, differences in physical activity and sedentary behavior with respect to sociodemographic and study related factors were examined. Methods A total of 4,351 students participated in an online survey. The amount of physical activity (metabolic equivalent of task-min/week) and the sitting time (h/day) were assessed using the German short form of the International Physical Activity Questionnaire. Differences in gender and age as well as field of study, targeted degree and study semester were analyzed using a single factorial ANOVA with Tukey correction or a Welch-ANOVA with Games-Howell correction. Results For physical activity, significant differences were found for gender (F(2, 80.46) = 17.79, p < 0.001, ηp2 = 0.009), for field of study (F(5, 1738.09) = 7.41, p < 0.001, ηp2 = 0.01), and for study semester (F(1, 948.12) = 5.53, p < 0.05, ηp2 =0.001), but not for age and targeted degree (p > 0.05). For sedentary behavior, significant differences were found for field of study (F(5, 3816) = 5.69, p < 0.001, ηp2 = 0.01) and targeted degree (F(3, 3868) = 3.94, p < 0.01, ηp2 = 0.003), but not for gender, age and study semester (p > 0.05). Conclusion Female students, students enrolled in “natural sciences, mathematics and informatics” and first year students appear to have an increased risk of an unhealthy lifestyle. Future research should identify barriers to and incentives of physical activity as well as reasons for high amounts of SB in sub-populations of university students. Suitable prevention and intervention programs are necessary.